Strategi Pemberdayan Klien IBM Melalui Program CSR PT Pertamina Integreted Terminal Cilacap bersama BNNK Cilacap di Desa Slarang - Nova Styaningrum; Azis Wahyono (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to describe and analyze the implementation of the Corporate Social Responsibility (CSR) program within the Community-Based Intervention (CBI) program. CBI is a program implemented by the National Narcotics Agency (BNN) to increase community involvement in drug rehabilitation services. This article also explains how to assist CBI clients (Individuals at Risk of Drug Problems) through the Corporate Social Responsibility (CSR) program implemented by the Cilacap National Narcotics Agency (BNNK) in collaboration with PT Pertamina Integrated Terminal Cilacap. This program aims to improve community life and reduce the likelihood of drug abuse among at-risk individuals. The empowerment methods used include skills training, health education, and social activities involving active community participation. By involving various parties, such as local governments and community organizations, this program aims to create a positive environment for the rehabilitation and social reintegration of CBI clients. The results of this CSR program indicate that public awareness of the dangers of drugs has increased, stigma against at-risk individuals has decreased, and skills have been developed that can help CBI clients find employment and avoid drug abuse. This article concludes that a community-based approach in PT Pertamina's CSR strategy can empower IBM clients and create a sustainable positive impact on society.